Critical reception of Charles Reade’s fiction in Russia in the 19th century; Язык. Общество. Образование - Сумцова О. В. Ольга Витальевна (2024, 2024)
The present article examines critical reception of the works by Charles Reade, the English writer of the Victorian period, in Russian literary studies in the 19th century. It is established that the writer’s literary activity has not received the in-depth and thorough critical comprehension in Russia despite Reade’s significant contribution to the formation of the native literary process